2018
DOI: 10.1016/j.celrep.2018.08.069
|View full text |Cite
|
Sign up to set email alerts
|

Nut Directs p300-Dependent, Genome-Wide H4 Hyperacetylation in Male Germ Cells

Abstract: Nuclear protein in testis (Nut) is a universal oncogenic driver in the highly aggressive NUT midline carcinoma, whose physiological function in male germ cells has been unclear. Here we show that expression of Nut is normally restricted to post-meiotic spermatogenic cells, where its presence triggers p300-dependent genome-wide histone H4 hyperacetylation, which is essential for the completion of histone-to-protamine exchange. Accordingly, the inactivation of Nut induces male sterility with spermatogenesis arre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
115
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(117 citation statements)
references
References 28 publications
2
115
0
Order By: Relevance
“…Until recently, very little was known regarding the normal function of NUTM1. It is now known to be critical for male fertility and is expressed in postmeiotic male germ cells where it recruits the HATs p300 and/or CBP and enables histone H4K5 and H4K8 acetylation . This stimulates the transcription of a subset of genes involved in transcriptional shutdown in preparation for the striking genome‐wide chromatin remodeling process within condensing spermatids, whereby histones are evicted and replaced by transition proteins and small basic proteins called protamines.…”
Section: Nutm1mentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, very little was known regarding the normal function of NUTM1. It is now known to be critical for male fertility and is expressed in postmeiotic male germ cells where it recruits the HATs p300 and/or CBP and enables histone H4K5 and H4K8 acetylation . This stimulates the transcription of a subset of genes involved in transcriptional shutdown in preparation for the striking genome‐wide chromatin remodeling process within condensing spermatids, whereby histones are evicted and replaced by transition proteins and small basic proteins called protamines.…”
Section: Nutm1mentioning
confidence: 99%
“…It is now known to be critical for male fertility and is expressed in postmeiotic male germ cells where it recruits the HATs p300 and/or CBP and enables histone H4K5 and H4K8 acetylation. 20 This stimulates the transcription of a subset of genes involved in transcriptional shutdown in preparation for the striking genome-wide chromatin remodeling process within condensing spermatids, whereby histones are evicted and replaced by transition proteins and small basic proteins called protamines. Notably, postmeiotic spermatids coexpress NUTM1 and the BRD family member bromodomain testis-specific protein (BRDT), 21 thus the megadomain-spanning chromatin hyperacetylation and transcriptional repression of genes involved in differentiation observed in NCs (see below) may be seen as a somatic aberration of this crucial male germline phenomenon.…”
Section: Nutm1mentioning
confidence: 99%
“…Recently it has been shown that Nut, a testis-specific factor exclusively expressed in post-meiotic cells, interacts with CBP/p300 HAT to enhance acetylation of H4 at both K5 and K8 [164] (Figure 5F). Interestingly, acetylation of histone H4 on residues K5 and K8 provides a binding site for the BRDT.…”
Section: Spermiogenesismentioning
confidence: 99%
“…In mammals, a near genome-wide histone removal occurs during the postmeiotic stages of spermatogenesis in specific cell types known as elongating and condensing spermatids. Histone removal is also preceded by a genome-wide histone acetylation, especially on H4 lysines 5 and 8 [1], creating a specific binding site for the first bromodomain of the testis-specific BET factor, Brdt. We previously demonstrated that Brdt is, in turn, required for histone removal, and is involved in the loading of transition proteins and protamines into nucleosomes [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Histone removal is also preceded by a genome-wide histone acetylation, especially on H4 lysines 5 and 8 [1], creating a specific binding site for the first bromodomain of the testis-specific BET factor, Brdt. We previously demonstrated that Brdt is, in turn, required for histone removal, and is involved in the loading of transition proteins and protamines into nucleosomes [1][2][3]. Our work on the involvement of histone variants in this process also led to the discovery of a series of testis-specific H2A and H2B histone variants as potentially interesting candidates in the control of postmeiotic male genome organization [4].…”
Section: Introductionmentioning
confidence: 99%